Senegal : Fourth Review Under the Policy Support Instrument and Request for an Extension of the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Senegal's Fourth Review Under the Policy Support Instrument (PSI) and Request for an Extension of the PSI. Performance under the PSI-supported program has been satisfactory, with all end-December 2016 assessment criteria and indicative targets met and four of the seven end-March 2017 indicative targets met. Of the five structural benchmarks set for the period from December 2016 to March 2017, three were met. Of the two unmet structural benchmarks, one was implemented with delay and one has not yet been implemented. The IMF staff recommends completion of the fourth PSI review and approval of the one-year extension of the PSI.